Toothpaste Formulation Ethanol Extract Mangosteen Peel (Garcinia mangostana L.) and Test Activity Against Candida albicans - Nur Khairun Nisa Junuda; Ermina Pakki; Nur Ida (Postgraduate, University of Mataram, 2023)
The mangosteen peel contains phenol compounds that have antifungal activity. The study aimed to find out the antifungal activity in the dosage form of toothpaste against Candida albicans. The research methods used include the extraction of mangosteen peel (Garcinia mangostana L.) by maceration using 96% ethanol. The toothpaste formula was composed with an extract concentration of 1.25% (F1); 2.5% (F2); 5% (F3); and base (B). Antifungal testing was carried out by diffusion method using Potato Dextrose Agar (PDA) media. The results showed that the toothpaste formula with a concentration of F1; F2; F3; and base (B) has an average value of successive inhibition zone diameters of 11.86 mm; 12.03mm; 12.54mm; and 7.78 mm. The conclusion of the study showed that the toothpaste preparation of the ethanol extract of mangosteen fruit peel (Garcinia mangostana L.) concentration was 1.25%; 2.5%; 5% which performs antifungal activity.